Employment Stress and Couple Adjustment among Clients With Disorders of Gambling and Alcohol Use: Themes of Transfers in Congruence Couple Therapy - Bonnie K Lee; Noor-Khanu Merali (SAGE Publishing, 2022)
Background: Individuals with problematic gambling, alcohol and substance use commonly report lower employment rates and more employment-related problems such as job loss, work conflicts and poor performance. Method: A thematic qualitative analysis was conducted to extract employment-related themes from 21 sets of addiction counselors' case notes of couple therapy sessions (average 10 sessions per case) from a randomized controlled trial of Congruence Couple Therapy (CCT). Case notes were examined for the types of employment issues to answer the research question: What are the interconnections of employment, couple adjustment and addictive behaviors as revealed in the CCT counselors' case notes? Results: Five key areas of employment-related stress were identified: (1) unemployment, (2) financial concerns, (3) history of crime, (4) overworking and workaholism, and (5) workplace conflict. These themes interacted negatively with couple adjustment and addictive behaviors. Using CCT as an intervention, clients gained skills in 4 areas transferred to employment: (1) awareness of self, other and family of origin, (2) congruent communication, (3) work-family balance, and (4) enlisting spousal support. These themes intersected with enhanced work functioning and reduced stress, alcohol use and gambling. Conclusion: Employment problems negatively impacted addictive behaviors, couple adjustment and well-being of partners and addicted clients. Skills and awareness gained in CCT promoted changes in addicted clients' employment functioning and coping with employment stress. The domains of work and couple adjustment are mutually influential in increasing or reducing stress with implications for addiction recovery. CCT as a viable intervention for enhancing employment function should be further studied.